Blended Learning and the Teaching of Writing - Mahfouz, Inas (2016)
This teacher research project focused on utilizing blended learning to teach writing to middle school students. The intervention was designed to fit into individual lessons needed to improve students’ writing skills with the main focus on sentence structure. Sixteen (16) 7th grade students were assessed with a writing sample applying the new skills they have learned. The intervention took a total of two weeks with six lessons implementing instruction. These lessons included a pre-assessment of student knowledge and a post assessment summarizing their gain of knowledge. The participants are from a small private school in the Midwest of the United States.